Intracranial Ameloblastoma Arising from the Maxilla: An Interdisciplinary Surgical Approach - Quick-Weller, Johanna; Koch, Felix; Dinc, Nazife; Lescher, Stephanie; Baumgarten, Peter; Harter, Patrick; Scheerer, Friedrich; Sader, Robert; Seifert, Volker; Marquardt, Gerhard; Freiman, Thomas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Ameloblastomas are a rare tumor entity accounting for only 10% of all odontogenic tumors. They mostly originate from the mandible. Only a few cases are known to grow aggressively and to invade the orbit, nasal cavity, or even the brain.Patient and Methods/Case Report We present the case of a 57-year-old patient who was admitted with a huge tumor involving the nasal cavity, the left maxilla, and the anterior fossa. Histologic diagnosis was made by biopsy. A combined two-stage neurosurgical maxillofacial approach was planned. First the intracranial tumor mass was removed using bifrontal trepanation. A duraplasty was sewn in to cover the brain. In the second procedure, a combined bifrontal and midfacial approach was used by craniofacial plastic surgeons and neurosurgeons. A perisinusoidal tumor mass and retropharyngeal tumor mass was removed up to the skull base. The left orbit was completely exenterated, and a fibular bone-muscle graft was used for palatal, orbital, and facial reconstruction. The facial vein and artery were carefully prepared to feed the bone-muscle graft by end-to-end anastomoses.Conclusion Ameloblastomas are very rare slow-growing tumors that show a tendency to recur. They are responsible for only 1% of all oral tumors. Their growth can be enormous, and they can extend into sinusoidal cavities, the orbit, and the brain. Complex and extensive palliative surgery can ease the concerns of these patients and prolong their survival.
Keywords: oral tumor; ameloblastoma; resection; bone-muscle graft; odontogenic tumor